Health-Related Quality of Life, Treatment Satisfaction and Adherence Outcomes of Haemophilia Patients Living in a German Rural Region - von Mackensen, Sylvia; Schleicher, Christian; Heine, Sabine; Graf, Norbert; Eichler, Hermann (Hämostaseologie, 2020)
In the context of the ‘Mobile Haemophilia Outpatient Care (MHOC)’ project we aimed to gather insights into the health-related quality of life (HRQoL), treatment satisfaction (TS) and adherence of persons with haemophilia (PWHs) who get treated at the Saarland University Hospital Haemophilia Treatment Centre (HTC). PWHs were visited at home at least twice (baseline, follow-up) by trained medical staff. Individual interviews were performed to measure patients' HRQoL and TS with validated questionnaires (Haem-A-QoL/Haemo-QoL and Hemo-SatA/Hemo-SatP). Socio-demographic and clinical data were collected. In total, 79 PWHs were enrolled; 56 adults with a mean age of 37.4 ± 16.4 years (17–78) and 23 children [mean age of 9.8 ± 4.2 years (3–16)]. In total, 62% were severely affected; 48.1% received prophylaxis. Patients reported good HRQoL (adults: 23.1 ± 17.1; kids: 24.3 ± 11.1). Patients (M = 11.2 ± 9.5) and parents (M = 14.3 ± 7.4) were very satisfied with their provided treatment. The majority of study participants were evaluated to have a good treatment adherence. After 1-year follow-up of the MHOC, a significant improvement in HRQoL was seen in adults (p < 0.033) and in proxy ratings of parents (p < 0.0001); TS remained high with no change by MHOC intervention. Patients reported good HRQoL and TS. Most of them were evaluated as having a good treatment adherence. After implementation of the MHOC, adult patients reported a better HRQoL. Such a mobile medical care service is considered beneficial for patients, especially with limited access to a HTC.
Keywords: haemophilia; haemophilia treatment centre; health-related quality of life; treatment satisfaction; adherence; adults; children